Influence of Smectic Liquid Crystallinity on Lamellar Microdomain Structure in a Main‐Chain Liquid Crystal Block Copolymer Fiber. Issue 20 (2nd August 2013) - Koga, Maito; Sato, Kazunori; Kang, Sungmin; Sakajiri, Koichi; Watanabe, Junji; Tokita, Masatoshi
<x xml:space="preserve">Abstract</x> The microlamellar and smectic liquid crystal (LC) structures of a block copolymer of a main‐chain LC polyester connected at both ends with poly(ethyl methacrylate) are investigated by fiber X‐ray scattering. In the as‐spun fiber, the lamellae are parallel to the fiber axis, while the smectic layers are perpendicular to it. Annealing the as‐spun fiber at a temperature higher than the isotropization temperature (Ti) of the LC segment preserves the lamellae, but the LC structure disappears. Further annealing the fiber at T < Ti improves the lamellar stacking coherence and aligns the smectic layers parallel to the lamellae. In contrast, annealing the as‐spun fiber at T < Ti conserves the smectic layers and arranges the lamellae in parallel to the smectic layers. Thus, the liquid crystallinity affects the lamellar ordering and orientation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>